Psychological stress and psoriasis: a systematic review and meta‐analysis4. (2nd March 2018) - Snast, I.; Reiter, O.; Atzmony, L.; Leshem, Y.A.; Hodak, E.; Mimouni, D.; Pavlovsky, L.
Summary: Background: Psychological stress has long been linked with the exacerbation/onset of psoriasis. Objectives: To determine if antecedent psychological stress is associated with the exacerbation/onset of psoriasis. Methods: A search of the PubMed, PsycINFO, Cochrane library and ClinicalTrials.gov databases was performed. Surveys evaluating beliefs about stress reactivity were analysed separately. Suitable studies were meta‐analysed. Results: Thirty‐nine studies (32 537 patients) were included: 19 surveys, seven cross‐sectional studies, 12 case–control studies and one cohort study. Forty‐six per cent of patients believed their disease was stress reactive and 54% recalled preceding stressful events. Case–control studies evaluating stressful events rates prior to the exacerbation ( n = 6) or onset ( n = 6) of psoriasis varied in time lag to recollection (≤ 9 months to ≥ 5 years). Pooling five studies evaluating stressful events preceding onset of psoriasis gave an odds ratio (OR) of 3·4 [95% confidence interval (CI) 1·8–6·4; I 2 = 87%]; the only study evaluating a documented stress disorder diagnosis reported similar rates between patients and controls (OR 1·2, 95% CI 0·8–1·8). Four studies evaluating stressful events prior to psoriasis exacerbation reported comparable rates with controls, whereas two found more frequent/severe preceding events among patients with psoriasis. A small prospective cohort study reported a modest association between stress levels and exacerbation of psoriasis ( r = 0·28, P < 0·05). Conclusions: The association between preceding stress and exacerbation/onset of psoriasis is based primarily on retrospective studies with many limitations. No convincing evidence exists that preceding stress is strongly associated with exacerbation/onset of psoriasis. Abstract : What's already known about this topic? It is common knowledge among patients with psoriasis and their physicians that psychological stress aggravates psoriasis. Numerous observational studies have suggested a link between preceding psychological stress and exacerbation and onset of psoriasis. What does this study add? A review of the current literature revealed that the association between preceding stress and psoriasis is built almost exclusively on retrospective studies with many limitations. To date, no convincing evidence exists that stress is strongly associated with psoriasis exacerbation and onset. This finding is psychologically beneficial for patients and has occupational and therapeutic implications. Linked Comment:  Dodoo‐Schittko. Br J Dermatol 2018;178 :1002 . Plain language summary available online